John Cookson, gunmaker. (2nd January 2022) - Weaver, David S.; Godwin, Brian
Abstract : The name John Cookson is associated with Lorenzoni-type magazine repeating flintlocks of high quality, assumed to have been made in London during the last decade or so of the 17th century. Nothing is known of this gunmaker. A John Cookson is known to have been a gunsmith in Boston during the first half of the 18th century and, while he is given credit in the US for inventing the magazine repeater, there is no evidence that he ever made such a gun in America. Over the years, there has been much speculation about a connection between these John Cooksons but none has ever been established. A recently discovered flintlock fowler signed Cookson appears to be late 17th century and shares a number of features which suggest manufacture by the same John Cookson who made the magazine repeaters. The paper examines the details of this fowler, comparing them to those of the known magazine repeaters and argues that they were all made by the same maker. An extensive archival search was also made of the John Cooksons of the UK and of Boston, the results of which are summarized here. While no direct connection could be established, the evidence strongly suggests that they were the same person.